Energy behavior in Karlsruhe and Germany - Martin Klarmann; Robin Pade; Wolf Fichtner; Nico Lehmann (Karlsruhe Institute of Technology (KIT), Institute for Industrial Production (IIP), 2022)
Climate change mitigation is one of the greatest human challenges. The associated transformation of energy supply and demand to low-carbon energy sources requires not only technical solutions, but also involves consumers and as such, represents a holistic societal process. To date, however, the energy-related behavior of consumers is poorly understood. Against this backdrop, energy panels may be a viable solution to monitor behavior and collect adequate data over long periods. Yet, consumer panels are often established at the local level, raising questions about whether a sample is representative of the population of interest. We take a first step into answering this question by comparing a local sample of household consumers from the Karlsruhe area in Southwest Germany with a sample from Germany. Our analyses are based on a sample of more than 1,000 respondents surveyed via computer-assisted telephone interviews (CATI) in summer 2021. Overall, the results show strong similarities between Karlsruhe and Germany, both in terms of sociodemographics and energy consumption behavior. Nonetheless, there are also differences between the two samples, for example, in terms of political orientation or climate concern. Future research should examine whether and to what extent these differences are relevant to subsequent analyses and how a panel can still be used to approximate the population under investigation.
Keywords: 330; Energy consumption; Citizen attitudes; Energy panel; Consumer behavior